Las TIC y las Mipymes costarricenses: Situación actual, retos y oportunidades. (ICTs and Costa Rica SMEs: current status, challenges and opportunities) - Picado Arroyo, Rytha (2013)
Las tecnologías de información y comunicación (TICs) han tenido un fuerte impacto en el desarrollo económico y social de los países. Costa Rica no se abstrae de esta realidad y muchos menos las micro, pequeñas y medianas empresas (Mipymes) por lo cual la Segunda Encuesta Nacional de Mipymes 2011 incursiona en temas de interés que relacionan el uso y aprovechamiento de las TIC. Este artículo resume los hallazgos más relevantes en las siguientes áreas: Internet, comercio electrónico, Internet en celulares y redes sociales.ABSTRACTSMEfinancing was one of the areas investigated in the Second National Survey ofmicro, small and medium sized Costa Rican companies during 2011. The most usedfinancing sources, credit applications during the last five years, end use ofthis credit, and current credit requirements in various financing institutionswere investigated. Similar to other countries, own funding was the main optionfor these companies. Thus, this work examines the conditions that facilitatethe use of self financing or other options available. Through statisticanalysis of the information collected, variables like initial funding source,previous experience of the entrepreneur and priority given to financialmanagement were shown to present a definite relationship to financingstrategies for Costa Rican SMEs.